PENGARUH TEKANAN KETAATAN, GENDER, KOMPLEKSITAS TUGAS, INDEPENDENSI, DAN PENGALAMAN AUDITOR TERHADAP AUDIT JUDGMENT - Irfan Priyoga; Sri Ayem (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
This study analyzes the influence of pressure obedience, gender, task complexity, independence, and auditor experience on audit judgment. The population in this study were auditors who worked in the financial supervision agency and the construction of representatives of special regions of Yogyakarta. The type of data carried out in this study is primary data. The data in this study which will be analyzed using an analysis tool consisting of data quality test, descriptive statistics, classical assumption test, and hypothesis testing with the help of SPSS version 16.0 program. the results of this study partially (t test), namely the pressure variable obedience, gender, and independence does not affect audit judgment. While task complexity variables and auditor experience have a significant positive effect on audit judgment. For simultaneous results (f test) together affect audit judgment.